Geração de energia por microturbina alimentada à biogás em uma propriedade rural: estudo de caso - Hirano, Marcio Yukio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The increasing energy demand and ongoing concerns with environmental issues such as global warning and the preservation of natural resources, has made manking seek, alternative sources of clean energy. In this scenario, the use of digesters on farms have meant an important step forward on energy, environmental and sanitarism issues, as waste from agriculture, mainly the creation of confinement on animals can be arranged properly. At the end of anaerobic biodigestion process can get three big value-added by-products: the biofertilizer, which is rich in nutrients; mineralized effluent, which can serve as a basis for the production of feed; and biogas, which is a fuel rich in methane gas. this work aims to present an analysis on the production of biogas through a digester on a farm intended for rearing dairly cattle, and the use of biogas in specific micro turbines to generate electricity, and the forms of energy use of gas the microturbine exhaust, in order to heat and cold. Also conducted and evaluation of the energy savings that the use of biogas adds to proertly. To prepare this report, data surveys have been conducted on the production and biogas composition commonly found in rural digesters, and technical information on microturbine, compressor, heat exchanger and liquid chiller with its manufacturers. At the end of this study, it was observed that it is possible to produce through the use of biogas microturbines in about 5,931 kWh per month to 11,751 kWh per month of electricity from organic waste collected from 240 dairly catle, which represents approximately 41-82% of the energy demand of rural property analyzed. Furthermore, through the use of heat of exhaust gas microturbine is possible to obtain 8.5 m3 per day of water at 95ºC which can be utilized to clean environments and equipment; or one may use the heated water from the heat recovery in a liquid cooler, it is possible to produce approximately 14.850 kMh per month of cooling...

A crescente demanda energética e as constantes preocupações com questões ambientais, como o aquecimento global e a preservação de recursos naturais, tem feito a humanidade buscar fontes alternativas de energias limpas. Neste cenário, o uso de biodigestores em propriedades rurais têm significado um importante avanço sobre questões energéticas, ambientais e de sanitarismo, pois os resíduos provenientes da agropecuária, principalmente da criação de animais em confinamento podem ser dispostos de maneira correta. Ao final do processo de biogestão anaeróbica é possível obter três subprodutos de grande valor agregado: o biofertilizantes, que é rico em nutrientes; o efluente mineralizado, que pode servir de base para a produção de ração; e o biogás, que é um gás combustível rico em metano. Este trabalho visou apresentar uma análise sobre a produção de biogás através de um biodigestor em uma propriedade rural destinado à criação de bovinos leiteiros, e o uso do biogás em microturbinas específicas para a geraão de energia elétrica, e as formas de aproveitamento energético dos gases de escape da microturbina, visando à produção de calor e frio. Também realizou uma avaliação sobre a economia de energia elétrica que o uso do biogás agrega à propriedade. Para a confecção deste trabalho foram realizados levantamentos de dados sobre a produção e a composição do biogás comumente encontrado em biodigestores rurais, e informações técnicas sobre microturbina, compressor, recuperador de calor e resfriador de líquido junto aos seus fabricantes. Ao final do presente estudo, pôde-se verificar que é possível produzir através do uso do biogás em microturbinas entre 5.931 kWh/mês a 11.751 kWh/mês de energia elétrica com os dejetos orgânicos recolhidos de 240 bovinos leiteiros, o que representa aproximadamente entre 41 a 82% da demanda energética da propriedade rural analisada. Além disso, através do..
Keywords: Biogas; Energia elétrica; Recursos naturais renovaveis